La surveillance et le contrôle de l’assurance générale au Québec - Bouchard, Jean-Marie (Assurances, 1986)
Given the seriousness of the situation, we have asked Mr. Jean-Marie Bouchard, General lnspector of Financial Institutions in Quebec, to describe the scope of his powers and of his dealings with insurers, firstly, to assess their current situation, secondly, to ensure that insurers are fulfilling their functions from a legal standpoint and, thirdly, to ascertain that their resources are always sufficient to cover their commitments. The article shows clearly that Mr. Bouchard is in the best position to determine the solvency of a company, assess the scope of its actions and implement the measures he feels are necessary. Indeed, he is perhaps the only person who can do so.